Insulinoma-associated Protein 1 (INSM1) Expression in Small Cell Neuroendocrine Carcinoma of the Urinary Tract. Issue 9 (October 2020) - Kim, Isaac E.; Amin, Ali; Wang, Li Juan; Cheng, Liang; Perrino, Carmen M.
Abstract : Clinical guidelines state that neoadjuvant chemotherapy should be administered before surgery in muscle invasive urinary bladder small cell neuroendocrine carcinoma. Recently described marker insulinoma-associated protein 1 (INSM1) has been reported to be sensitive and specific for neuroendocrine differentiation, however, its efficacy in urinary tract small cell carcinoma is not well established. This study examines immunohistochemical expression of INSM1 on whole tissue sections of urinary tract small cell neuroendocrine carcinoma and compares INSM1 expression with established neuroendocrine markers. Immunohistochemical stains for CD56, INSM1, synaptophysin, and chromogranin were performed on 32 cases of small cell neuroendocrine carcinoma of the bladder. Staining was scored for intensity (0: no staining; 1: weak; 2: moderate; 3: strong) and proportion of cells stained (0: 0%; 1: >0% to ⩽25%; 2: >25% to ⩽50%; 3: >50% to ⩽75%; 4: >75% to 100%). INSM1 was positive (intensity 1 to 3 or proportion 1 to 4) in 87% (28/32) of cases (20 with intensity 2 to 3, 17 with proportion 3 to 4). CD56, synaptophysin, and chromogranin were positive in 75% (24/32), 60% (19/32), and 44% (14/32) of cases, respectively. INSM1 was negative (n=4) or only showed weak intensity staining (n=7) in 34% (11/32) of cases. INSM1 is a sensitive marker of small cell neuroendocrine differentiation of the urinary tract. However, this study suggests that optimal utilization of INSM1 would be inclusion in a limited panel of stains rather than as a stand-alone screening marker given that it is negative or only shows weak intensity staining in a significant proportion of cases.